ANALISIS KOMPARASI FATWA DSN NO. 21/DSN-MUI/X/2001 TENTANG TAKAFUL TERHADAP PROGRAM BPJS KESEHATAN - Ali, Nazra; Nugroho , Ario; Kurniawan , Faizs; Yusuf Nasution , Rahmanda; Putera Lubis , Gusrianda Tri; Fauzan Andika , Muhammad; Nur Iqbal, Muhammad (Gapenas Publisher, 2025)
This study aims to analyze comparatively the implementation of the BPJS Kesehatan program with takaful principles, by taking a case study at the Mitra Babussalam Clinic, Besilam. The background of this research departs from the question of the compatibility of the national social security system, especially BPJS Kesehatan, with sharia values believed by the majority of Muslims in Indonesia. This study uses a qualitative approach with data collection techniques through interviews with clinic managers and literature review on the concept of sharia insurance. The results of the study show that BPJS Kesehatan and sharia insurance have similarities in terms of social goals, the principle of help-help (ta'awun), and non-profit nature. However, there are fundamental differences in contract structure, fund ownership, management system, and supervision. BPJS Kesehatan does not use sharia contracts explicitly and is not supervised by the Sharia Supervisory Board, as is the case in the takaful system. Nevertheless, the service practices at Babussalam Clinic show the application of ethical values and services in accordance with Islamic principles. This study recommends that BPJS Kesehatan consider integrating sharia values in its system to answer the needs of the Muslim community and increase public trust in national social security.